Literature Review: pola makan dan kualitas diet pada remaja dan dewasa dengan HIV/AIDS - Shella Putri Ferari; Siti Rahayu Nadhiroh (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Human Immunodeficiency Virus (HIV) infection remains an unresolved health problem in Brazil. Diet plays an important role in the immune system of HIV/AIDS patients because adequate amounts of macronutrients and micronutrients are important. Food quality has also been used as a proxy for predicting the risk of death and chronic diseases. Measuring diet quality is an indicator that can describe a person's dietary practices in accordance with the dietary recommendations set out to be able to live healthily.Objective: This study aimed to analyze the dietary patterns and diet quality of adolescents and adults with HIV/AIDS.Methods: This study was a systematic literature review. The protocol used in the systematic literature review of this study used the PRISMA method. The SLR protocol and evaluation were performed using the PRISMA method to select research articles that had been found. The PRISMA method collects articles from PubMed, Google Scholar, Research Gate, SINTA, Garuda, and Scopus databases. The search terms used were Indonesian and English. The search terms used in Indonesian were "Diet and HIV/AIDS" OR "Diet Quality and HIV/AIDS". The search terms in English were "dietary habit and HIV/AIDS" OR "diet quality and HIV/AIDS". The articles collected were published between  2014  and  2022.Results: According to the findings of a systematic literature review, consumption patterns that do not meet the needs of HIV infection will lead to chronic malnutrition and AIDS, resulting in a drastic decrease in resistance to other infections. Diet plays an important role in the immune system of HIV/AIDS patients, because adequate intake of macro-and micronutrients is essential for normal functioning. Diet quality is influenced by the diversity of food ingredients and food security, which remains low. Diet quality in HIV/AIDS patients affects their body weight, mental health status, physical health status, CD4 count, and other health problems.Conclusion: Dietary habits do not meet intake requirements due to HIV infection, which causes chronic malnutrition and, at the AIDS stage, results in a drastic decrease in resistance to other infections. Diet quality in HIV/AIDS patients affects their body weight, mental health status, physical health status, CD4 count, and other health problems.